Interaksi Sosial Etnis Lokal dan Etnis Tionghoa dalam Pencegahan Konflik di Kota Makassar - Isnaeni Dian Imanina K; A Rahim; Muhajir K (JED (Jurnal Etika Demokrasi), 2018)
This study aims to determine the form of social interaction between Local Ethnicity and Chinese Ethnicity in the city of Makassar, to find out the impact of local social and ethnic Chinese interactions in conflict prevention in Makassar City and also to know the role of the government in the process of social interaction in preventing inter-ethnic conflict in Makassar city. This type of research is qualitative descriptive research. Data collection techniques are interviews, documentation and observations. The data analysis technique was carried out in a qualitative descriptive manner. The results of this study indicate that the form of social interaction between Local Ethnicity and Chinese Ethnicity in Makassar City is cooperation, competition, accommodation and assimilation. Social interactions that occur between Local Ethnicity and Chinese Ethnicity cause social impacts which are positive impacts that lead to cooperation and negative impacts that lead to conflict or conflict. The government plays a very important role in reducing and resolving the turmoil that has the potential for conflict by negotiating, mediating and facilitating.Keywords : Social Interaction, Local Ethnicity, Chinese Ethnicity and Prevention Conflict